Anatomical Therapeutic Chemical / Define Daily Dose antibiotik bronkopneumonia pediatri di RS Roemani Muhammadiyah - Maharani Dewi, Rissa; Maprillia , Nanda; Nastiti , Nindita Sari (Journal of Pharmaceutical and Sciences, 2024)
The increase in repeat hospitalizations after the covid19 pandemic with bronchopneumonia diagnoses in pediatric patients is the first rank. Therapeutic management was associated with the length of hospitalization. Pediatric bronchopneumonia is the case with antibiotic therapy. Current guidelines recommend first-line and alternative options in the management of antibiotic therapy for pneumonia in hospitalized pediatric patients. Empirical broad-spectrum antibiotic therapy for acute infections with consideration of the common etiology of possible pneumococcal involvement The risk of resistance increases with the massive use of antibiotics. The study had an observational descriptive design with retrospective data collection from 280 samples of pediatric patients, aiming to evaluate the use of antibiotics with the ATC/DDD method. Based on empirical selected therapy DDD (Define Daily Dose)/100 patient days, the quantity of antibiotics that are widely used is ceftriaxon 38.36 DDD /100 patient days followed by Cefoperazon sulbactam 3.88 DDD /100 patient days, Cefotaxime 3.77 DDD /100 patient days, Gentamicin 2.57 DDD /100 patient days, Amikacin 1. 70 DDD /100 patient days, Azithromycin 0.76 DDD /100 patient days, Ampicillin Sulbactam 0.50 DDD /100 patient days, Cefixime 0.27 DDD /100 patient days, and Meropenem 0.13 DDD /100 patient days. Drug data included in DU90% are Ceftriaxon, Cefoperzon Sulbactam, Cefotaxime. From the research conducted, the highest DDD/100 patient days value was Ceftriaxon. DDD value indicates high use of antibiotics, does not mean unreasonable use of drugs, so a qualitative review must be done.